"Perdon" / "pardon": False Variation and Textual Transmission Problems in the Corpus of Secular Galician-Portuguese Lyric Poetry - Ferreiro, Manuel (Madrygal. Revista de Estudios Gallegos, 2016)
One of the problems facing editors of secular Galician-Portuguese lyric poetry is the misreading or misinterpretation of certain forms and sections due to an imperfect process of manuscript transmission. As an illustration of this, as well as the challenges faced by editors trying to create a sound and accurate reconstruction of the original text, this article will examine the apparent variation between the words perdon and pardon in the Galician-Portuguese cantiga manuscripts transmitted in Italian apographs. This comprehensive analysis of the occurrence of pardon in the corpus of secular Galician-Portuguese troubadour poetry demonstrates that the presence of the alternative form is due, not to variation, but to an inexact rendering on the part of a scribe in Cancioneiro da Biblioteca Nacional. A similar need for emendation is also revealed in relation to other false variant forms introduced by the same scribe and reproduced uncritically in most subsequent editions (perfiar / parfiar, per / par).